(untitled) (Revista Iberoamericana de Bioética, 2018)
The decision to undergo medically assisted reproduction techniques involves a series of ethical questions that men and women of all times have had to answer: why do so? Wwho decides? Why so? Why not? How to face the process? We look at History to help them respond from the experience of so many women and couples who have needed to react toattend their impossible reproduction with the most unlikely resources. Looking at the subject and theirhis experience of meaning may be a more fruitful bioethical proposal than resorting toducing reflecting solely onion only to techniques.